Application of solvent demulsification dispersive liquid–liquid microextraction for nicotine and cotinine measurement in human urine combined with hydrophilic interaction chromatography tandem mass spectrometry. Issue 29 (13th July 2017) - Wang, Qian; Yuan, Yue; Li, Mingxin; Chen, Yaqian; Man, Yi; Dard, Michel; Zou, Xiaoli
Abstract : A SD-DLLME-HILIC-MS method was established and applied for human urinary nicotine and cotinine measurement to evaluate tobacco exposure. Abstract : A method for the determination of urinary nicotine and cotinine by solvent demulsification-dispersive liquid–liquid microextraction (SD-DLLME) combined with hydrophilic interaction chromatography tandem mass spectrometry (HILIC-MS/MS) was established. The chromatographic separation was performed on an ACQUITY UPLC® BEH HILIC column with an isocratic elution in which methanol and 0.1% ammonia (v/v) were used as the mobile phase. Identification was conducted using tandem mass spectrometry with electrospray ionization in positive mode. Working calibration curves were plotted for quantification determination. DLLME conditions were optimized with the orthogonal array design (OAD). The microextraction was performed with 100 μL trichloromethane as the extracting solvent and 1000 μL methanol as the dispersing solvent. In addition, the pH value of the sample solution was adjusted to 9.0 for good extraction efficiencies. 800 μL acetone was selected as the demulsification solvent to facilitate the phase separation between the sample solution and extractant. The method detection limits of nicotine and cotinine were 0.0025 μg L −1 and 0.0020 μg L −1 respectively. Besides, during the sample preservation, it was proved that 1% (w/v) of sodium hydrogen sulfate in the sample can prevent analyte degradation. The established method was applied to analyze 516 urine samples. The method was simple, sensitive and accurate, and it also meets the requirement of evaluating human tobacco exposure, especially for the nonsmoking population.